Simulasi Sistem Pelayanan Rawat Jalan Pasien menggunakan Simulasi Kejadian Diskrit (Des) - Della Zilfitri Zubir; Felka Andini; Muhammad Ridho; Yosep Filki (Jurnal Informatika Ekonomi Bisnis, 2022)
The hospital is one of the health service centers that play an important role in society. Health Centers must provide the best service for their patients. In practice, good or excellent service is not easy to realize because of various factors that exist in the field which are probalistic in nature. To maintain service quality, it is necessary to carry out evaluation, analysis, and improvement activities on the existing system. Evaluation, analysis, and improvement activities on the system can be carried out using system simulations with the aim of producing better services. This research was conducted in an outpatient service system using discrete event simulation with the help of promodel software. The purpose of this study is to apply a discrete event simulation model in outpatient services so that there is an improvement in outpatient services and the efficiency of existing human resources. The simulation results show that the simulation model used is valid and can be used to evaluate the outpatient service system.